Spectral and directional sensitive composition characterization of mixed-radiation fields with the miniaturized radiation camera MiniPIX Timepix2. (1st November 2022) - Granja, C.; Jakubek, J.; Soukup, P.; Jakubek, M.; Turecek, D.; Marek, L.; Polansky, S.; Gajewski, J.; Rucinski, A.; Stasica, P.; Rydygier, M.; Novak, A.; et al.
Abstract: The semiconductor pixel detector Timepix2 is operated with highly integrated readout electronics as a miniaturized and portable MiniPIX TPX2 radiation camera for radiation imaging and spectral-sensitive particle tracking in wide field-of-view. The device provides room-temperature operation, ease of use (single USB 2.0 port), online response with single track visualization, fast frame readout (up to 60 fps) and double per-pixel response for detailed measurements with per-pixel energy and counting or energy and timing sensitivity. We evaluate the response and applicability of a MiniPIX TPX2 camera with the Timepix2 ASIC chip equipped with a 300 µm thick silicon sensor for wide-range composition and spectral characterization of mixed-radiation fields. Measurements were performed in high-energy proton radiotherapy environments with protons of selected energies in the range 225–70 MeV and water-equivalent targets of varying configuration (size, dimension, geometry). High-resolution pattern recognition and spectral-tracking analysis of the single particle tracks in the pixelated detector enable to resolve and classify all detected signals according particle species, direction and energy loss. Based on the experimental calibrations performed with well-defined radiation fields together with quantum imaging visualization of single particle tracks, ten broad-range particle-event classes are resolved. Mixed-radiation fields are thus analyzed according particle-event types in wide range of deposited energy, linear-energy-transfer LET, particle fluxes and dose rates. The spatial distribution over the detector sensor matrix of the distinguished groups can be visualized as well as the directional mapping of energetic charged particles.